A LYUBERTSY STUDY OF MORTALITY AMONG PATIENTS WITH PRIOR ACUTE MYOCARDIAL INFARCTION: THE FIRST RESULTS OF THE LIS STUDY - S. Yu. Martsevich; M. L. Ginzburg; N. P. Kutishenko; A. A. Deev; A. V. Fokina; E. V. Daniels (Klinicist)
Objective: to study late disease outcomes in patients with prior myocardial infarction (MI).Subjects and methods. The study enrolled 1133 patients admitted with diagnosed acute MI in the Lyubertsy District, Moscow Region, over 3 years(2005–2007). Inhospital mortality rates were analyzed. An attempt was made to establish the patients’ life status. The fate of 111 (10 %) patientswas unclear. There were 172 deaths at the hospital; 191 patients died after discharge from hospital (an average follow-up of 1.3 years).Results. The vast majority of patients died from coronary heart disease in the late period, which allows these deaths to be associated with prior MI and the late prognosis of life to be regarded as very serious in these patients.